The Three Must-Get-Theres Based on the Novel by Alexandre Dumas - Nelissen, Maud (Lobster Films, 2014)
The career of influential comedian Max Linder was nearing its end when he directed and starred in this burlesque of Douglas Fairbanks' "Three Musketeers". As Dart-in-Again, Linder plays an hilarious spoof of the Fairbanks character. He is a peasant's son who rides his donkey, Jazbo, to Paris to make his fortune. Upon his arrival, he meets the three Must-Get-Theres - Walrus (Jack Richardson), Octopus (Charles Metzetti) and Porpoise (Clarence Werpz). They all battle the forces of the evil Duke of Rich-Lou (Bull Montana). Dart-in-Again comes to the aid of the Queen (Catherine Rankin), and her seamstress, Connie (Jobyna Ralston, Harold Lloyd's future co-star). He retrieves the Queen's brooch from her lover, Bunkumin (Harry Mann) and saves her honor. For his heroic acts, Dart-In-Again is rewarded by the King (Frank Cooke), who makes him a full member of the Must-Get-Theres. He also weds Connie and all ends well. Unfortunately, things didn't end so well for Linder in real life - three years later, he and his wife would commit suicide because his career was in a shambles. [www.allmovie.com]
Keywords: DVD-Video